(untitled) (Revista científica Olimpia, 2021)
Research carried out in different sports has shown that the results achieved in the athlete’s Preparation are linked to the quality which the training process has been developed on scientific bases. The research addresses the influence of biological control on the sports Performance of athletes whose objective was to characterize morphologicaly the athletes of Graco-Roman wrestling and provide the necessary guidelines for the individualization of training. The 14 athletes of the Graco-Roman wrestling team, category 13-15 years of the EIDE “Lino Salabarría” of the Sancti Spíritus province, were taken as a sample, representing 100% of the population of that sport in this category; Anthropometric measurements such as: height, weight, skin folds of the biceps, triceps, subscapularis, suprailiacum and calf, elbow and knee diameters, and contracted arm and leg circumferences were performed on them. With the data obtained, the somatotype and body composition were determined, which served to provide guidance to the coaches on the aspects to take into account in the training planning of each athlete. In general, all the parameters measured in the research improved from one measurement to another, which brought with it an increase in functional possibilities, it was found that the biomedical control carried out allowed the best individualization of the training and with it better sports results, verifying the importance of biological control during the training process.